Towards understanding the effects of climate change on the sweetpotato insect pests Acraea acerata Hewiston and Cylas puncticollis Boheman and their management in Africa - Okonya, J. (2024)
In tropical Africa, the sweetpotato butterfly Acraea acerata, is a major endemic pest of sweetpotato (Ipomoea batatas (L.) Lam.). Outbreaks of A. acerata have been reported by farmers in Uganda to be more frequent than in the past 10 years. It is therefore speculated that global warming may be responsible for this increased risk of outbreaks and abundance (damage potential). The develop temperature-based phenology model of A. acerata developed in Chapter 5.1 using the Insect Life Cycle Modeling (ILYCM) software was implemented in the potential population distribution and risk mapping module to analyze and map the potential establishment, abundance and spread on global and regional scales using three indices (establishment risk index, ERI-, generation index GI, and activity index, AI). Interpolated WorldClim data and downscaled data of the SRES-A1B scenario were applied for the current (year 2000) and for future climates (year 2050) temperature conditions and scenarios, respectively. The establishment risk index (ERI) values predicted by the model under the current climatic conditions compare well to the current distribution of A. acerata (ERI=1.0) in Africa. For most of Africa, the simulated number of generations per year of 8-12 under climatic conditions of the year 2000 are in the range of those reported in literature. For some regions of West African countries, a slight reduced risk of establishment is predicted by the year 2050 while East and Central African countries will potentially have an increased risk of establishment by A. acerata. Under the 2050 scenario, an increase by 1-5 generations per year is predicted for most of the African countries where sweetpotato is cultivated. An increase in the number of generations implies an increase in the pest abundance resulting into higher infestations and crop losses. A. acerata is an increasing threat for sweetpotato production in Africa and therefore a risk for food security of sweetpotato producing households. It is therefore vital to inform policy makers about these potential changes and risks to prevent invasions and establish adaptation plans for effective pest management. This analysis confirms that higher temperatures due to global warming will contribute to more frequent A. acerata outbreaks and abundances in Africa but will also facilitate its distribution and establishment in many other sweetpotato growing countries. There is need to include pest risk mapping results in adaptation planning to manage future pest risks at global, regional, and country level.